FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN COVID-19 DI KOTA BOGOR - Reynanda Nadhira Rinaldi (2021)
Bogor City is an area that has a high risk of transmission of the COVID-19 virus. According to the Health Protocol Compliance Monitoring Survey, Bogor residents only have a protocol against the health protocol in the range of 61-75%. The purpose of this study was to determine the risk factors associated with the incidence of COVID-19 in Bogor City in 2020. This study used a cross-sectional quantitative analytical design. The sample of 110 people consisted of Bogor residents who had conducted a PCR Swab Test based on surveillance data at the Bogor City Health Office and Bogor Puskesmas with a purposive sampling technique. Bivariate data analysis using Chi-Square and multivariate data analysis using multiple logistic regression (α = 0.05). Bivariate research shows that risk factors associated with the incidence of COVID-19 include gender, comorbidities, frequency of visits to public places, duration of being outside the home, use of public transportation, safe distance surveillance, habits, smoking habits, and alcohol habits. Based on the results of the multivariate analysis, male respondents have a risk of being infected with COVID-19, according to the assessment of female respondents with a POR of 4,916 (95% CI: 2,162-11,180) and the frequency of respondents visiting public places more than 3 times a week at risk for COVID-19 infection of respondents who have never visited a public place in a week with POR 11,797 (95% CI: 4,343-32,042). Respondents who are male and respondents who visit places more than 3 times are at general risk of being infected with COVID-19 in Bogor City